Human Resource Management Practices as Determinants of Job Satisfaction Among College Instructors at St. Cecilia’s College-Cebu, Inc. - Mark Delmie Basalo; Angel I. Canonigo; Chierelyn Chavez; Kissy Mae C. Emperado; Jeannelie Luz N. Macapil; Michaela C. Maglasang; Mary Joy Mortejo; Mark Anthony N. Polinar; Regin M. Suarez (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This descriptive-correlational study explored the relationship between HRM practices and job satisfaction among thirty-six (36) college instructors at St. Cecilia’s College-Cebu, Inc. during the academic year 2025–2026. Only instructors with at least two years of teaching experience participated in evaluating the school’s HRM practices. The data were analyzed using descriptive statistics, Spearman’s rho, and multiple regression. The results showed that three HRM areas—Training and Development (r = 0.716), Compensation and Benefits (r = 0.793), and Performance Management (r = 0.714)—significantly predict job satisfaction. Among these, Compensation and Benefits and Performance Management emerged as the strongest predictors, highlighting the importance of fair compensation, competitive benefits, and transparent evaluation systems in improving morale and employee retention. Instructors expressed appreciation for fair performance evaluations and constructive feedback. However, they also noted the need for clearer promotion guidelines and more collaborative goal-setting processes. Overall, the findings confirm that effective HRM practices have a meaningful impact on faculty job satisfaction. Based on these results, the study recommends several actions. Training and Development programs should be strengthened through regular workshops, mentoring initiatives, and external training opportunities. Compensation and Benefits should be reviewed through salary benchmarking, the introduction of non-monetary incentives, and clearer communication of policies. Lastly, Performance Management systems should be refined by updating evaluation procedures, clarifying promotion standards, and encouraging shared goal-setting between administrators and faculty members. Implementing these improvements is expected to enhance faculty satisfaction, increase retention, and support the institution’s long-term effectiveness.